2015
DOI: 10.1089/bfm.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Obesity and Breastfeeding Noninitiation in the United States: An Examination of Racial and Ethnic Differences

Abstract: Prepregnancy BMI is a significant predictor for breastfeeding noninitiation for non-Hispanic white and non-Hispanic black women. Further exploration of the differences underlying the association between prepregnancy BMI and breastfeeding behaviors among racial subpopulations of women in the United States is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 40 publications
1
33
2
5
Order By: Relevance
“…The characteristics of included studies are summarized in Table . Most were conducted in the USA , with some in Europe , Australia and one in Canada . Sample characteristics were reported infrequently; of 20 included studies, 13 reported participant ethnicity or race , 9 reported mean age and 5 reported mean BMI .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies are summarized in Table . Most were conducted in the USA , with some in Europe , Australia and one in Canada . Sample characteristics were reported infrequently; of 20 included studies, 13 reported participant ethnicity or race , 9 reported mean age and 5 reported mean BMI .…”
Section: Resultsmentioning
confidence: 99%
“…Yet, epidemiological studies provide consistent evidence of lower breastfeeding initiation and/or duration for mothers who were overweight and obese prior to pregnancy 8–12. Moreover, some suggest that the relationship between BMI and breastfeeding may be moderated by ethnicity,8 11 and there is emergent evidence that underweight may also be negatively correlated with breastfeeding 8…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding rates are associated with maternal BMI. Compared with women of normal body weight, breastfeeding is less likely to be initiated in women with overweight or obesity , and obese mothers are less likely to maintain breastfeeding , even after adjusting for psychosocial and demographic factors such as social and emotional support, breastfeeding knowledge, behavioural beliefs and confidence .…”
Section: Four Pillars Of Women Infants and Children Servicementioning
confidence: 99%